Uniform and Robust Nuclear Expression of HES1 in Neuroendocrine Neoplasms. (December 2019) - Cui, Min; Cai, Zhenjian; Awadallah, Amad; Xin, Wei
Introduction . Neuroendocrine neoplasms (NENs) are neoplasms that most commonly arise from gastrointestinal tract, pancreas, and lung. HES1 is a downstream target of Notch signaling pathway. The current literature about HES1 expression in NENs is sparse and inconsistent. Methods . In this study, we evaluated HES1 expression by immunohistochemistry in a total of 32 cases of NENs, including 13 well-differentiated neuroendocrine tumors from gastrointestinal tract, 10 cases of well-differentiated neuroendocrine tumors of pancreas, 9 cases from lung, including 4 cases of typical carcinoid, 1 case of atypical carcinoid, and 4 cases of neuroendocrine carcinoma. The intensity of the stain was scored from − to +++, and the distribution of the staining of HES1 was evaluated. Results . HES1 demonstrates uniform robust (+++) nuclear staining pattern in the tumor cells of all the NENs (32/32), regardless of the origin of the system and the grade of the tumor. Conclusions . HES1 is uniformly expressed in NENs with robust nuclear expression pattern. Our finding suggests that NOTCH1 or HES1 inhibitor is a potential therapeutic choice for neuroendocrine neoplasms.